relationship between learning styles and language instruction skills of high school students - javad solleymanpoor (Institute of Management fekrenoandish, 2019)
Paying attention to learning styles and its determining components [determinants] for students plays a crucial role in teaching and education of today's world. Therefore, the current study's goal was to explore the relations between learning styles (with respect to its basic components) and language learning skills (English language). For this purpose, statistical population of this research is a total of 1260 male students from high schools in Chalous province among which 154 subjects are selected randomly, by Morgan-Krejcie's Table. This research is conducted based on Vermont and Rijswijk's theory (for assessment of learning styles) and language learning skills (the skills of listening, speaking, reading and writing) in English language. Main tool for data collection is standardized questionnaire of learning styles, and data analysis of current research is done by using of Pearson coefficient and stepwise regression. Results from this research indicate that all learning styles have a positive and direct relationship with language learning skills, but two types of learning styles, namely decentralized with a coefficient of 0.497 and meaning and goal based learning style with a coefficient of 0.283 has got the highest importance. Hence it can be said that for as much enhancement and comprehension as possible, if educational system considers decentralized and meaning and goal based learning styles, it will be more helpful for students to achieve the language learning skills. In the other word, importance of learning styles' role recognition in anticipating of students' language learning skills is confirmed.